2022
DOI: 10.1002/jctb.7016
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of cyanotoxins in El Guajaro Reservoir, Colombia using a microalgae‐based consortium MPMC

Abstract: BACKGROUND Cyanobacteria blooms occur in freshwater and saline ecosystems under certain environmental conditions, such as eutrophication, that are often accompanied by the production of cyanotoxins; Those biological toxins are a risk to the health of animals and humans. The eutrophication of water bodies is becoming more frequent due to organic pollution pressure from swage discharge, so outcrops are frequent and difficult to manage by the communities affected by these phenomena. Most of the control mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The widespread eutrophication of water bodies has significantly increased the frequency of algae/cyanobacteria blooms in China. Decomposing algae/cyanobacteria blooms consume a massive amount of dissolved oxygen in water [1,2], resulting in deteriorated water quality [3]. In addition, Microcystis aeruginosa is one of the cyanobacteria most prone to blooms [4].…”
Section: Introductionmentioning
confidence: 99%
“…The widespread eutrophication of water bodies has significantly increased the frequency of algae/cyanobacteria blooms in China. Decomposing algae/cyanobacteria blooms consume a massive amount of dissolved oxygen in water [1,2], resulting in deteriorated water quality [3]. In addition, Microcystis aeruginosa is one of the cyanobacteria most prone to blooms [4].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Banda et al 11 performed physiological and kinetic evaluations of a denitrifying sludge using ampicillin as the only electron source, showing that denitrification processes allow the simultaneous oxidation of recalcitrant compounds and nitrate reduction during wastewater treatment. Gutiérrez et al 12 reported that bioaugmentation with microalgae can be used to avoid the predominance of cyanobacteria in water bodies, reducing the risk of cyanotoxins for animals and humans.…”
mentioning
confidence: 99%